2018
DOI: 10.3166/phyto-2018-0106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activities of Organic and Aqueous Extracts of Northeast Algerian Marrubium vulgare

Abstract: Marrubium vulgare (Lamiaceae) is frequently used in traditional medicine to treat many illnesses from ancient times. Its beneficial effects include antibacterial, antioedematogenic, and analgesic activities. This study was designed to evaluate the antioxidant and anti-inflammatory activities of organic and aqueous extracts of the leaves, the flowers, the stems, and the roots of Marrubium vulgare. The total phenolic and flavonoid contents as well as the antioxidant and the anti-inflammatory effects of methanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Yields of extraction and the amounts of polyphenols and flavonoids in different extracts of Marrubium vulgare are presented on table 1. These results are concordant with those of M. vulgare harvested from Bordj Bouariridj region 20 except for the flavonoid content of stems extract which is higher (11.72 versus 5.21 mg QE/g). It was aimed in this work to identify some of the phenolic compounds present in the methanolic extracts of M. vulgare using HPLC which is a high-resolution chromatographic technique probably the most widely used analytical technique for characterizing the polyphenolic compound 23 .…”
Section: Polyphenol and Flavonoid Contentssupporting
confidence: 88%
See 1 more Smart Citation
“…Yields of extraction and the amounts of polyphenols and flavonoids in different extracts of Marrubium vulgare are presented on table 1. These results are concordant with those of M. vulgare harvested from Bordj Bouariridj region 20 except for the flavonoid content of stems extract which is higher (11.72 versus 5.21 mg QE/g). It was aimed in this work to identify some of the phenolic compounds present in the methanolic extracts of M. vulgare using HPLC which is a high-resolution chromatographic technique probably the most widely used analytical technique for characterizing the polyphenolic compound 23 .…”
Section: Polyphenol and Flavonoid Contentssupporting
confidence: 88%
“…In fact, the plant is reported to possess antihypertensive 16 , vasorelaxant 17 , hepatoprotective 18 and antibacterial 19 properties. We have previously demonstrated that M. vulgare extracts exhibit antioxidant activities by their ability to scavenge free radicals, inhibit lipid peroxidation and chelate metals 20 . Furthermore, our results indicate that this plant has powerful effects in the inhibition of the release of inflammatory mediators anti-inflammatory cytokines such as TNF-ɑ, IL-1β and IL-8.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the number of total cells counted in the Balf was considerably increased in the Mae group, suggesting the implication of this remedy in the inhibition or suppression of inflammatory factors and by preserving almost all the cells of the alveolar-capillary wall and the alveolar lumen. 31 These results were confirmed by those of the histological study which showed histopathologic changes representing the most specific and characteristic variables accompanying pulmonary fibrosis. In this context, the microscopic observations following the HE and TR staining showed an enormous arrangement of collagen especially at the level of the alveolar septum, inflammatory infiltrate, and histiocytes in the BLM group.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, the choice of Mae is based above all on its anti-inflammatory and antioxidant effects played by the high content of total polyphenols (73.619 mg EGA/g extract compared to other horehound extracts of different origins: Serbia; 54.65 ± .87; 29 Morocco; 5,45 ± 0,08, 30 and Algeria; 48.62 ± 1.73 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation